Ms Pengaruh Model Pembelajaran Project Based Learning Berbantuan AI Dalam Meningkatkan Kreativitas Dan Hasil Belajar Siswa - intan goyanda; Ahmad Ridoh; Fauziah Fauziah (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
Abstract The quick growth of technology, especially Artificial Intelligence (AI), has created new chances to help exciting learning methods. Still, students studying Visual Communication Design (DKV) at SMK Negeri 1 Bungo often don’t show much creativity in their design projects, which affects how well they learn. This research wants to look into how Project Based Learning (PjBL) that uses AI influences students’ creativity and their results in the Basic Principles of Design class. The study used a type of research called quasi-experimental with a design that includes only posttests and a control group that wasn’t equal. The sample included 58 students, split into an experimental group with 30 students and a control group with 28 students. The tools used for the research were a creativity survey and a test for measuring learning achievement. The data was examined using a test for independent samples called the t-test. The results show that using the PjBL model with AI helped boost both the creativity of the students and their learning results a lot. Moreover, students in the experimental group showed more creativity and had better learning results than those in the control group. Therefore, it can be said that using the PjBL model with AI is effective in enhancing the creativity and learning results of DKV students at SMKN 1 Bungo.